Small animal dermatology : - Hill, Peter B. (Butterworth-Heinemann, 2002)
Skin disease is one of the most common reasons why dogs and cats are presented to veterinarians and yet dermatological diagnosis and treatment can often prove troublesome. To minimise problems, clinicians must take a logical and systematic approach to carrying out appropriate tests, make an accurate clinical diagnosis and then apply the necessary treatment. Small Animal Dermatology explains all of the processes involved, taking a problem-based approach to diagnosis and then proceeding to a step-by-step explanation of appropriate tests, highlighting techniques that ensure accurate interpretation of results. Colour line illustrations provide a valuable aid to diagnosis. Small Animal Dermatology: A practical guide to the diagnosis and management of skin diseases in dogs and cats is an invaluable purchase for practitioners who wish to improve their diagnostic accuracy when dealing with these common conditions, as well as an essential aid for veterinary students who are beginning to learn about skin diseases and their manifestations.